Responsibilisation and leadership in the neoliberal university: a New Zealand perspective. Issue 1 (2nd January 2017) - Amsler, Mark; Shore, Cris
ABSTRACT: We examine how discourses of leadership and responsibilisation are used in contemporary universities to deepen neoliberal administration and further the corporate university's business plan by restructuring and redescribing academic work. Strategically, responsibilisation discourse, promoted as 'distributed leadership', is a technology of indirect management. Responsibilisation language stipulates 'expectations' for workers and integrates academic work (teaching, learning, research, service) into an administered regime recognising and rewarding successful conduct ('leadership') in the university. We intervene in this responsibilisation discourse by critically analysing texts about distributed leadership in one New Zealand university context. Linking Foucault's analysis of earlier forms of liberal governmentality with critical discourse analysis, we explore how administrative structures, power relations, and regulating management discourse seek to reshape employee behaviour in the neoliberalised, post-democratic university. We present a case study of one university's 'Leadership Framework', which exemplifies a new form of 'post-neoliberal governmentality' in higher education, embedding self-governance within increasingly instrumentalising centralisation.